On The Poems in Naṣīḥat al-Mulūk’s Chagatai Translation - Mamura Mamatkulova; Zühal Ölmez (Türkiyat Mecmuası)
Naṣīḥat al-Mulūk, which was written in Persian during the years 1105-1111 by Imam Ghazzālī, was translated into Chagatai in 1509 by the order of Temur Sultan, the son of Shaybani Khan. Its translator was Sayyid Ali Kātib from Balkh. Under the title of stories and wisdom in Naṣīḥat al-Mulūk, advice and counsel are given to the administrators. To reinforce this advice, verse fragments were used. Some of these poems are translated as verse, while others are translated as prose in the Arabic and Ottoman translations of the work. Sayyid Ali Kātib, who translated Naṣīḥat al-Mulūk into Chagatai, translated the prose parts of the work expertly and also tried to translate the verse parts while trying preserving the original Persian work. However, while translating the poems, Sayyid Ali Kâtib demonstrated his mastery over the works of Chagatai by compiling the appropriate couplets from the famous Chagatai poets. To translate prose parts, Sayyid Ali Kātib used Chagatai poems, especially Navā’ī’s, masterfully and without disturbing the integrity of the text, and made his work different from the translations of Naṣīḥat al-Mulūk into other languages. The aim of this study was to examine the verse pieces, types, sources in Chagatai Naṣīḥat al-Mulūkin terms of their relation to the subject of the original work.